2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Daily Repetitive Transcranial Magnetic Stimulation for Poststroke Upper Limb Paresis in the Subacute Period

Abstract: Our results suggest that dailyhigh-frequency rTMS of the ipsilesional M1 is tolerable and modestly facilitates motor recovery in the paralytic hand of subacute stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 29 publications
(57 reference statements)
3
65
0
2
Order By: Relevance
“…There was significant improvement in the hand function of both groups immediately after the combined therapy and at 2 weeks after combined therapy. This result was consistent with that of a previous study in which the grip strength of the affected hands was improved from the baseline only in the conventional therapy with real rTMS group compared to the conventional therapy with the sham rTMS group [ 23 ]. Our results could reinforce the evidence that low-frequency rTMS with hand training during the aftereffect period has positive effects on hand function.…”
Section: Discussionsupporting
confidence: 93%
“…There was significant improvement in the hand function of both groups immediately after the combined therapy and at 2 weeks after combined therapy. This result was consistent with that of a previous study in which the grip strength of the affected hands was improved from the baseline only in the conventional therapy with real rTMS group compared to the conventional therapy with the sham rTMS group [ 23 ]. Our results could reinforce the evidence that low-frequency rTMS with hand training during the aftereffect period has positive effects on hand function.…”
Section: Discussionsupporting
confidence: 93%
“…Although some studies have shown benefits of early rTMS at the activity and participation levels [45, 46], their outcome measures may be contaminated by compensatory movements, limiting conclusions about effects on true reorganization [44]. Also excluded from discussion are studies that use subjective appraisals, such as visible muscle twitch to determine stimulation intensity [47, 48], as this limits replication and could lead to inconsistent neural modulation and behavioral response.…”
Section: Human Rtms Trials In Early Strokementioning
confidence: 99%
“…Many studies were designed to stimulate the inhibition of the contralateral nonaffected primary motor area 3-12 months after a stroke, that is, during the chronic stage [5]. Daily high-frequency rTMS of the ipsilesional M1 is tolerable, and modestly facilitated motor recovery in the paralytic hand of subacute stroke patients [4]. Many studies in Japan found improved motor function of the upper limbs in chronic stroke patients [12,16].…”
Section: Tdcs Study In Post-stroke and Parkinson's Diseasementioning
confidence: 99%
“…Improvement of patients postinfarction occurs spontaneously within the first 3 months. Many studies on light to moderate paralysis using rTMS, there are no significant improvement that measure tool used in a study [4]. Improvement of patients postinfarction occurs spontaneously within the first 3 months and, in studies of light to moderate paralysis, the effectiveness of rTMS as evaluated by STEF and other such tools was not clear.…”
Section: Tdcs Study In Post-stroke and Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation